Homeownership through asnaf home financing in Malaysia: An empirical investigation - Hanudin Amin (Emerald, 2024)
The purpose of this study is to examine asnafs’ acceptance of home financing in Malaysia. Design/methodology/approach – This work developed and introduced the Maqasid theory of consumer behaviors (MTCB) to examine the effects of educational programmers, mortgage welfare, consumer justice and Islamic debt policy on receptiveness. Data analysis involving 733 respondents was conducted using partial least squares (PLS), where SmartPLS4.0 software comes into play. Findings – In the core model, the effects of the MTCB’s variables helped shape the development of asnaf home financing acceptance. Research limitations/implications – This study was based on quantitative data and geographical constraints. Practical implications – The findings provide valuable inputs for the Joint Committee Body (JCB), combining Islamic banks and State Islamic Religious Councils to develop action plans for improving the facility offered. Social implications – This work functioned as a social benchmark for improving Islamic home financing that includes asnafs’ homeownership. Originality/value – A new conceptual framework for asnaf home financing drawn from MTCB is developed in the context of asnafs’ homeownership